SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF SCHIFF BASE DERIVED FROM GLYCINE AND 4-CHLOROBENZOPHENONE AND ITS METALS COMPLEXES OF Cr(II) and Co(II) - Khalid, Halima; Hussaini, Sunusi Y.; Hasheem, Khatan A.; Panda, Najib A. (FUDMA JOURNAL OF SCIENCES, 2022)
The Schiff base ligand was synthesized using glycine and 4-chlorobenzophenone, and then reacted with metal salt of chromium, and cobalt to form the complex of the metals. The ligand and the complexes were characterized using IR-spectrophotometer, and peaks were analysed which confirmed the formation of (M-N) and (M-O) bond in the complexes at around 503- 847, also solubility test, water of crstallisation, magnetic susceptibility, melting Point and conductivity of the ligand and complexes were carried out in the research. Lastly, the compound were tested against some strain of bacteria(Salmonella typhi, Staphylococcus aureus, Escherichia coli) in which the activity of the ligand and some complex were detected in the bacteria, the cobalt complex showed higher activity than the chromium complex and the ligand.